Study on chaos phase space synchronous rotation and distinguish switching security communication - Guang-ming SUN; Jin-jie HUANG (Tongxin xuebao)
A new chaotic dynamic system was proposed and the dynamic of this system was analyzed.Through the research of balance point,Lyapunov index,Lyapunov dimension and Poincare section,the chaotic behavior of the system was approved.Z axis of chaos system phase space was researched.Z axis rotation model in the phase space was built through introducing rotation matrix,and chaos system space synchronous rotation was researched.Based on the research results above,a chaotic distinguish switching security communication system was presented for the communication of information security.